Percolation behavior in morphology and modulus of polymer blends - Hsu,W. .; Wu, S.
The tensile property of a plastic/rubber blend depends critically on the morphology and connectivity of the two phases. At low plastic volume fractions, the plastic phase forms isolated domains in the matrix of rubber phase, and the tensile property of the blend is largely controlled by the continuous rubber phase. As the plastic volume fraction increases, the plastic phase gradually connects into a pervasive network that eventually dominates the tensile and shear properties of the blend. The transition of the blend from a rubber-dominated to a plasticdominated behavior is a manifestation of percolation transition. The plastic volume concentration at which the transition takes place is the percolation threshold. Its dependence on morphology is discussed by contrasting the behaviors of anisotropic injection-molded specimens vs. isotropic compression-molded specimens of the two-phase blends of an amorphous thermoplastic polyester, PETG, and an ethylene-propylene-diene rubber, EPDM. It is found that the tensile modulus just above the percolation threshold obeys a power law as a function of the plastic volume concentration in excess of the percolation threshold. By analyzing the longitudinal tensile modulus of injection-molded PETG/EPDM specimens just above the threshold, it is shown that the scalar elastic percolation theory of de Gennes is at work here. For compression-molded PETG/EPDM specimens, it is found that the isotropic tensile modulus over the entire composition range obeys the symmetric effective medium theory